Designing virtual reality exposure scenarios to treat anxiety in people with epilepsy: Phase 2 of the AnxEpiVR clinical trial - Lewis-Fung, Samantha; Tchao, Danielle; Gray, Hannah Gabrielle; Nguyen, Emma; Pardini, Susanna; Harris, Laurence R.; Calabia, Dale; Appel, Lora (Frontiers in Virtual Reality, 2023)
Anxiety in people with epilepsy (PwE) is characterized by distinct features related to having the condition and thus requires tailored treatment. Although virtual reality (VR) exposure therapy is widely-used to treat a number of anxiety disorders, its use has not yet been explored in people with epilepsy. The AnxEpiVR Pilot Study represents the first effort to design and evaluate the feasibility of VR exposure therapy to treat anxiety in PwE. This paper describes the results of the design phase (Phase 2) of the AnxEpiVR Pilot Study, which involved creating a minimal viable product of customizable and hierarchical VR exposure scenarios using 360o video technology. Through participatory design methods and incorporating feedback from people with lived experience (n = 5) over multiple iterations, we aimed to create a VR exposure therapy program that 1) is safe for this population, 2) has a high level of fidelity and 3) would be appropriate for treating a broad range of fears related to epilepsy/seizures. The final product includes three exposure scenarios: (A) Social Scene - Dinner Party, (B) Public Setting - Subway, and (C) Public Setting - Shopping Mall. Each scenario contains seven five-minute scenes of varying intensity, from which a subset may be chosen and ordered to create a customized hierarchy based on appropriateness to the individual’s specific fears. Elements used to intensify scenes include increasing social demands, potential for physical danger, specific triggers, and epilepsy-related content (e.g., first-person simulation of a seizure). Strengths and limitations using 360o video for designing exposure scenarios and future directions for testing and refining the product are described.